Formation of Stripped Stars from Stellar Collisions in Galactic Nuclei - Charles F. A. Gibson; Fulya Kiroğlu; James C. Lombardi Jr.; Sanaea C. Rose; Hans D. Vanderzyden; Brenna Mockler; Monica Gallegos-Garcia; Kyle Kremer; Enrico Ramirez-Ruiz; Frederic A. Rasio (The Astrophysical Journal)
Tidal disruption events (TDEs) are an important way to probe the properties of stellar populations surrounding supermassive black holes. The observed spectra of several TDEs, such as ASASSN-14li, show high nitrogen-to-carbon (N/C) abundance ratios, leading to questions about their progenitors. Disrupting an intermediate- or high-mass star that has undergone CNO processing, increasing the nitrogen in its core, could lead to an enhanced nitrogen TDE. Galactic nuclei present a conducive environment for high-velocity stellar collisions that can lead to high mass loss, stripping the carbon- and hydrogen-rich envelopes of the stars and leaving behind the enhanced nitrogen cores. TDEs of these stripped stars may therefore exhibit even more extreme nitrogen enhancement. Using the smoothed particle hydrodynamics code StarSmasher , we provide a parameter space study of high-velocity stellar collisions involving intermediate-mass stars, analyzing the composition of the collision products. We conclude that high-velocity stellar collisions can form products that have abundance ratios similar to those observed in the motivating TDEs. Furthermore, we show that stars which have not experienced high CNO processing can yield low-mass collision products that retain even higher N/C abundance ratios. We analytically estimate the mass fallback for a typical TDE of several collision products to demonstrate consistency between our models and TDE observations. Lastly, we discuss how the extended collision products, with high central to average density ratios, can be related to repeated partial TDEs like ASASSN-14ko and G objects in the Galactic center.